Effect of Locality and Diameter Class on Chemical Composition of Quercus leucotrichophora A. Camus Ex Bahadur Seeds - Singh, Bhupinder; Deol, G. S. (Indian Forester, 1985)
Ban oak seeds collected from different sized tree. (dbh 25-75 cms) from three localitles were analysed for starch, crude protein, fat, tannin and ash content. Crude protein, fat and ash content varied with the localities. A locality at median elevation in the altitudinal range of the species (Matasa) showed higher amount of these constituents than those at lower or higher altitudes. All the chemical constituents were highest in lowest diameter class and showed a consistent decrease with increase in diameter of trees.